Development Of Banana Stem Extract Cream Formulation (Musa Acuminata X Musa Balbisiana) As An Antioxidant - Sugiarti Windarsih; Kartika Sari (International Journal of Health Engineering and Technology, 2026)
According to the Central Statistics Agency for 2021, this year's banana harvest reached 2.39 million tons. Banana tree trunk waste has been thrown away, but it turns out it has the potential to be used as a cosmetic product. If you want to achieve the desired effect from a preparation, you must use the right formulation. The aim of this research is to obtain a cream preparation formula containing jackfruit banana tree stem extract that is safe, effective and stable. The research method used was an experimental method. Making the extract used the maceration method with 70% ethanol solvent. The cream preparation formula is made from jackfruit banana tree trunk extract, namely formulas 1, 2 and 3, the formula process uses the method of melting and mixing the ingredients and active substances. An evaluation was carried out on the cream preparation and its stability was tested, including observing homogeneity, measuring pH, organoleptics, testing the type of emulsion, testing the stickiness of the cream and testing the spreadability. In the physical evaluation, creams F0, F1, F2 and F3 meet the physical stability requirements. Meanwhile, the stability test for F1 and F2 creams was unstable after 1 month of storage. Based on the research results, it can be concluded that jackfruit banana tree stem extract can be formulated into a cream preparation.